Promotion of herbal medicine in the use of medicinal plants with neurological action: an integrative review (Research, Society and Development, 2021)
This research aimed to explain what types of protocols are applied to the use of medicinal plants in the performance of the nervous system, in addition to analyzing the effectiveness and safety of medicinal plants that act on the neurological system. For that, the electronic databases MEDLINE/PUBMED, LILACS and SCIELO were used, which after exclusion and inclusion criteria were obtained x studies. The results showed that: Cymbopogon citratus and Melissa officinais had sedative and calming effects against insomnia and nervousness. Curcuma longa L shows therapeutic potential in the treatment of several diseases, including the central nervous system, Passiflora incarnara L. indicated a potential anxiolytic and sedative effect, Lavandula officinalis is used as an essential oil for use through aromatherapy, showing a calming sedative effect, Petiveria alliace L. demonstrates performance on the central nervous system. It is concluded that despite the therapeutic potential of medicinal plants against central nervous system disorders, few updated studies were found that assess the pharmacological action of these medicinal plants. It is noteworthy that this study promotes a correlation between popular knowledge and the various forms of application of scientific knowledge of these medicinal plants.